2018
DOI: 10.1002/cam4.1753
|View full text |Cite
|
Sign up to set email alerts
|

BCRABL1 transcript levels at 4 weeks have prognostic significance for time‐specific responses and for predicting survival in chronic‐phase chronic myeloid leukemia patients treated with various tyrosine kinase inhibitors

Abstract: The present study aimed to assess the clinical impact of BCR‐ABL1 transcript levels determined at an earlier time point than the 3‐month early molecular response (EMR) in chronic‐phase chronic myeloid leukemia (CML‐CP) patients. BCR‐ABL1 transcript levels of CML‐CP patients (n = 258; median age, 43 [range, 18‐81] years) treated with various tyrosine kinase inhibitors (TKIs) were determined at 4 weeks (28 ± 3 days) and at every 3 months of treatment initiation. At 4 weeks, receiver operating characteristic curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…The diminishing prognostic role of FLT3 ‐ITD mutations under contemporary therapy in AML has been underlined in a recent report and underscores the need to account for not only response to but also type of induction chemotherapy, in assessing prognostic relevance 11 . Regardless, the observations from the current study highlight the value of considering post‐treatment variables as formal components of survival prediction in AML, a concept that is also being pursued in acute lymphoblastic leukemia 12,13 and chronic myeloid leukemia 14–16 . In this regard, it should be noted that CR/CRi is a morphologic definition whose value as a prognostic marker might be further enhanced by targeting molecular or cytogenetic remission, as well as assessment of minimal residual disease (MRD); unfortunately, MRD data were not readily available in the current retrospective study 17,18 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The diminishing prognostic role of FLT3 ‐ITD mutations under contemporary therapy in AML has been underlined in a recent report and underscores the need to account for not only response to but also type of induction chemotherapy, in assessing prognostic relevance 11 . Regardless, the observations from the current study highlight the value of considering post‐treatment variables as formal components of survival prediction in AML, a concept that is also being pursued in acute lymphoblastic leukemia 12,13 and chronic myeloid leukemia 14–16 . In this regard, it should be noted that CR/CRi is a morphologic definition whose value as a prognostic marker might be further enhanced by targeting molecular or cytogenetic remission, as well as assessment of minimal residual disease (MRD); unfortunately, MRD data were not readily available in the current retrospective study 17,18 .…”
Section: Discussionmentioning
confidence: 67%
“…11 Regardless, the observations from the current study highlight the value of considering post-treatment variables as formal components of survival prediction in AML, a concept that is also being pursued in acute lymphoblastic leukemia 12,13 and chronic myeloid leukemia. [14][15][16] In this regard, it should be noted that CR/CRi is a morphologic definition whose value as a prognostic marker might be further enhanced by targeting molecular or cytogenetic remission, as well as assessment of minimal residual disease (MRD); unfortunately, MRD data were not readily available in the current retrospective study. 17,18 The prognostic value of CR/CRi, 19 as well as that of MRD response, 20,21 in AML, has also been shown in patients treated with less intensive drug regimens, such as combination of hypomethylating agents and venetoclax.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors suggested as a possible solution to this debate the measure of the slope of the BCR-ABL1 transcript reduction: indeed, in the group of cases with a BCR-ABL1/ABL1 ratio >10% at 3 months, the outcome was better for those who showed a halving time <79 days, that could represent a favorable reduction kinetics that could prelude to the achievement of the optimal response at the second time-point (6 months) (36, 37). Similarly, another promising approach could be the measurement of BCR-ABL1 transcript after only 4 weeks of treatment: in a series of 258 cases, the Receiver Operating Characteristic (ROC) curve showed that patients with a BCR-ABL1/ABL1 ratio <41% after 1 month of therapy had higher probabilities of achieving the optimal response at 3 months, DMR (56 vs. 29%) and presented longer EFS (93 vs. 85%) (38).…”
Section: Real-time Quantitative Pcr: Its Fundamental Role In Managemementioning
confidence: 99%